Effect of a mouthrinse containing rice peptide CL(14-25) on early dental plaque regrowth: a randomized crossover pilot study. (December 2015) - Takayama, Saori; Kato, Tetsuo; Imamura, Kentaro; Kita, Daichi; Ota, Koki; Suzuki, Eiichi; Sugito, Hiroki; Saitoh, Eiichi; Taniguchi, Masayuki; Saito, Atsushi
Abstract Background We aimed to evaluate clinically the effect of mouthrinse containing a rice peptide on early dental plaque regrowth. Methods The study was designed as a double-masked, two-group crossover randomized pilot trial, involving 10 periodontally healthy volunteers. After receiving a professional tooth cleaning at baseline, over the next 3 days each participant refrained from all oral hygiene measures and had two daily rinses with 20 ml of the test mouthrinse containing 0.4 % rice peptide CL(14-25) or placebo rinse. At the end of each experimental period, plaque score was assessed using the modified Volpe's method, and the participants filled out a questionnaire. Each participant underwent a 7-day washout period followed by a second allocation. The plaque score was the primary outcome of the study and participant perception was the secondary outcome. Results No adverse effects were observed in the participants during the study. Clinically, the mean plaque score of the examined teeth was significantly lower in the test group (2.44 ± 0.74, CI: 1.91–2.96) than the placebo group (2.65 ± 0.63, CI: 2.20–3.10) (P  < 0.05). When analyzed according to the type of teeth, a significantly lower score of the premolars/molars was observed in the test group (2.39 ± 0.68, CI: 2.08–2.71) than that in the placebo group (2.66 ± 0.58, CI: 2.39–2.93) (P  < 0.05). Conclusions The mouthrinse containing 0.4 % rice peptide CL(14-25) was effective in reducing the early regrowth of dental plaque. However, clinical relevance of this efficacy needs to be validated in a future large-scale study. Trial registration: UMIN Clinical Trials Registry (UMIN-CTR) R000014000. Date of formal registration: November 1, 2013.